Productivity and competitiveness: The case of football teams playing in the UEFA Champions League - Espitia-Escuer, M.; Garcia-Cebrian, L. I. (Athens Journal of Sport, 2016)
The purpose of this study is to evaluate the competitive situation of the UEFA Champions League in relation to other entertainment alternatives. As tools of analysis, Malmquist indices for the football teams that have participated in the UEFA Champions League among the years 2003-2011 will be calculated. The Malmquist index measures the change in productvity whereas the efficiency ratios used for the calculation of the former were found by applying a Data Envelopment Analysis (DEA). The relationship between productivity and competitiveness in an economic sector is as follows: an increase in productivity allows the remuneration of the factors to be increased without having to raise the price of the product offered. The UEFA Champions League may see its competitiveness threatened in relation to other entertainment alternatives, because participating teams do not show a clear increase in productivity.